Pengaruh E-Trust dan E-Service Quality Terhadap E-Loyalty Pengguna Layanan Mobile Banking Bank Umum Syariah - Nengsih, Novia; Septianna, Syifa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research aim to determine the influence of e-trust and e-service quality on the e-loyalty of mobile banking users at Islamic commercial banks. This research employs a quantitative research method. The sampling technique used is purposive sampling. The data analysis techniques employed include testing the research instrument, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the R² test. The results of the study indicate that e-trust has a significant influence on the e-loyalty of mobile banking users at Islamic commercial banks. Furthermore, e-service quality also has a significant influence on the e-loyalty of mobile banking users at Islamic commercial banks. Moreover, e-trust and e-service quality together have a significant effect on e-loyalty.. Based on the results of the coefficient of determination (R Square) test, a value of 0.505 or 50.5% was obtained. This indicates that e-trust and e-service quality together explain 50.5% of the variability in e-loyalty of mobile banking users at Islamic commercial banks, while the remaining 49.5% is influenced by other variables not included in this study.